2016
DOI: 10.2196/mhealth.5202
|View full text |Cite
|
Sign up to set email alerts
|

Parent Use and Efficacy of a Self-Administered, Tablet-Based Parent Training Intervention: A Randomized Controlled Trial

Abstract: BackgroundParent training programs are traditionally delivered in face-to-face formats and require trained facilitators and weekly parent attendance. Implementing face-to-face sessions is challenging in busy primary care settings and many barriers exist for parents to attend these sessions. Tablet-based delivery of parent training offers an alternative to face-to-face delivery to make parent training programs easier to deliver in primary care settings and more convenient and accessible to parents. We adapted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 29 publications
4
90
0
Order By: Relevance
“…Under these assumptions, a sample size of 68 parents (34 interventions; 34 controls) in each of four sites for a total sample size of 272 will provide power of 0.80 to detect differences in the analysis of intervention effects on parent and child outcomes. A previous study of the group-based Chicago Parent Program had a reported attrition rate of 13% over 12 months [7] and our pilot study had an attrition rate of 4% over 6 months [17]. Although attrition in the pilot study was quite low, we conservatively estimated attrition to be 13% over 12 months; therefore, we will recruit a total sample size of 312 at baseline.…”
Section: 41mentioning
confidence: 96%
See 2 more Smart Citations
“…Under these assumptions, a sample size of 68 parents (34 interventions; 34 controls) in each of four sites for a total sample size of 272 will provide power of 0.80 to detect differences in the analysis of intervention effects on parent and child outcomes. A previous study of the group-based Chicago Parent Program had a reported attrition rate of 13% over 12 months [7] and our pilot study had an attrition rate of 4% over 6 months [17]. Although attrition in the pilot study was quite low, we conservatively estimated attrition to be 13% over 12 months; therefore, we will recruit a total sample size of 312 at baseline.…”
Section: 41mentioning
confidence: 96%
“…Our power calculation is based on an effect size of d = 0.31, α 2-tailed =0.05, an intracluster correlation (ICC) of 0.50 across repeated assessments. The effect size was established from analysis of parent outcomes from our pilot study of the ezParent program [17]. Using data from the pilot study, ICCs for outcome variables ranged from 0.65-0.78 over three assessments.…”
Section: 41mentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions reduce reliance on harsh discipline, and reduce child behavior problems before they become chronic and entrenched (National Academies, 2016). In fact, many of these evidence-based parenting programs have been developed and implemented by nurses, including the Chicago Parent Program (Breitenstein et al, 2012; Gross et al, 2009); ezParent Program (Breitenstein, Fogg, Ocampo,Acosta, & Gross, 2016); the Incredible Years Program (Webster-Stratton et al, 1997); and Insights (McClowry,Snow, Tamis-LeMonda, & Rodriguez, 2010). All of these programs provide parents with skills to strengthen the quality of the parent-child relationship and reduce problematic behaviors without reliance on harsh discipline.…”
Section: Three Exemplars Of Child Povertymentioning
confidence: 99%
“…A recent randomized control trial (RCT) of a mobile health intervention (ezPARENT) aimed at promoting parenting competence and preventing child behaviour problems among children aged 2–5 showed that the intervention was engaging (Breitenstein, Brager, Ocampo, & Fogg, ), acceptable and feasible (Breitenstein, Fogg, Ocampo, Acosta, & Gross, ). Another recent pilot study of mobile health intervention (Children Eating Well‐CHEW) aimed at reinforcing nutrition education and help prevent childhood obesity among children aged 2–4 showed moderate to high usability and feasibility of the intervention (Hull et al., ).…”
Section: Introductionmentioning
confidence: 99%